KAJIAN JARAK LEGOWO TERHADAP IKLIM MIKRO PADA BUDIDAYA PADI SISTEMJAJAR LEGOWO - I Putu Hendra; Sumiyati Sumiyati; I Wayan Tika (Jurnal BETA (Biosistem dan Teknik Pertanian), 2014)
This study was conducted to determine the legowo distance studies in rice farming systems legowo row. This study is also expected to get the optimal distance legowo on legowo row planting system to improve the productivity of rice in Subak system. This research is divided into 5 treatment, the treatment in accordance with local farmers distance of 28 cm ; legowo 6:1 with wide legowo 1.25 x 28 cm ; legowo 6:1 with wide legowo 1.50 x 28 cm ; legowo 6:1 with wide legowo 1.75 x 28 cm ; legowo 6:1 with wide legowo 2 x 28 cm. This study was repeated 3 times. Parameters observed in this study ware : microclimate include: ambient temperature (T) , relative humidity (RH ), solar intensity (I). The production of a broad unity. In addition, the observed range of roots. The results suggest the application of legowo 6:1 cropping systems with a wide range legewo difference in each treatment shown to affect the relative humidity (RH), solar radiation, and air temperature. The results were obtained with a wide range of treatment legowo 1.75 x 28 cm is the best treatment with the highest yield among other treatment that is equal to 7.41 ton / ha.